1986
DOI: 10.1172/jci112574
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous expression of the c-sis gene and release of a platelet-derived growth factorlike molecule by human alveolar macrophages.

Abstract: Alveolar macrophages from normal individuals and patients with interstitial lung diseases spontaneously expressed a 4.2-kilobase mRNA complementary to the c-sis gene, a proto-oncogene coding for one of the chains of platelet-derived growth factor (PDGF). Concomitantly, these cells released a mediator with the properties of PDGF, including: (a) chemotactic factor for smooth muscle cells whose activity was resistant to heat and acid, but sensitive to reduction; (b) mitogenic (competence) activity for fibroblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(51 citation statements)
references
References 40 publications
4
47
0
Order By: Relevance
“…tinct growth factors that bind to heparin. One of these HBGFs elutes from immobilized heparin with 0.5 M NaCI and can be shown to be PDGFlike, confirming earlier reports of macrophagederived PDGF (Shimokado et al, 1985;Mornex et al, 1986). The evidence that the HBGF eluting at 0.5 M NaCI is PDGF-like includes coelution with human PDGF on immobilized heparin columns, neutralization of growth activity by antisera that neutralize PDGF, inactivation by disulfide reducing agents, and resistance to heating at 100°C.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…tinct growth factors that bind to heparin. One of these HBGFs elutes from immobilized heparin with 0.5 M NaCI and can be shown to be PDGFlike, confirming earlier reports of macrophagederived PDGF (Shimokado et al, 1985;Mornex et al, 1986). The evidence that the HBGF eluting at 0.5 M NaCI is PDGF-like includes coelution with human PDGF on immobilized heparin columns, neutralization of growth activity by antisera that neutralize PDGF, inactivation by disulfide reducing agents, and resistance to heating at 100°C.…”
Section: Introductionsupporting
confidence: 84%
“…Macrophages produce many growth factors, possibly more than any other cell type. Among the well-characterized macrophage-derived growth factors are platelet-derived growth factor (PDGF) (Shimokado et al, 1985;Mornex et al, 1986), basic fibroblast growth factor (bFGF) (Baird et al, 1985), transforming growth factoralpha (TGF-a) (Madtes et al, 1988), transforming growth factor-beta (TGF-fl) (Assoian et al, 1987), interleukin-1 (IL-1) (Hazuda et al, 1988;Schmidt et al, 1984), and tumor necrosis factoralpha (TN F-a) (Leibovich et al, 1988). Additional macrophage-derived growth factors have been reported but they have yet to be fully characterized and purified (Madtes et aL, 1988;Singh et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages might therefore be implicated in promoting tumour growth in these circumstances but the point is not proven. If this potentiation were secondary to the increased numbers of macrophages then it might be because of the many types of polypeptide growth factors they produce -including PDGF and EGF (Leslie et al, 1984;Hamburger & White, 1986;Nordan & Potter, 1986;Morne et al, 1986;Rich, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that activated human alveolar macrophage secrete PDGFs Mornex et al, 1986;Shimokado et al, 1985). Thus, postnatally, PDGF appears to be one of the factors available to the alveolar macrophage for mediating normal lung defense and lung in¯ammation .…”
Section: Discussionmentioning
confidence: 94%